Ultrasonography findings in retinopathy of prematurity - a pilot study - Foo, Lee Kok (2010)
1. To describe the fundus findings in different stages of ROP. 2. To determine the ultrasonographic B-scan findings in different stages of ROP. 3. To determine the association between clinical fundus findings and ultrasonographic B-scan findings in different stages of ROP. Descriptive cross sectional study. A total of 90 eyes of 47 patients with different stages of ROP were recruited in this study. All patients’ clinical diagnosis was established by ophthalmoscopic examination. The ultrasound examinations were performed within 2 days of ophthalmoscopic examination and clinical diagnosis was masked. All eyes were examined with 10 MHz ultrasound system with eye closed with instillation a drop of topical anaesthetic. A total of 12 meridians (position according to clock hour) images of each eye were taken. The images were analyzed and identified of different ultrasonic features indicative of ROP stages. In this study, 37 eyes in Stage 1, 29 eyes in Stage 2, 18 eyes in Stage 3 and 3 eyes in Stage 4 and 5 respectively were recruited. All ultrasonography stages of ROP were studied. 91.1% of Stage 1 has negative sign. 3 eyes (9.1%) at stage 1 has stage 2 ultrasound findings. In Stage 2, 58.6% of eyes have ultrasound findings of “shallow retinal thickening and ridge” and 41.4% of eyes have negative sign. 66.7% of eyes at stage 3 showed “broad retinal thickening and giant ridge”, 5.5% of stage 3 showed stage 2 ultrasound signs and 27.8% of stage 3 has negative sign. All eyes at stage 4 and 5 have an excellent ultrasonographic detection. The clinical findings were strongly correlated to ultrasound findings of all five stages in our study (Pearson R = 0.83,/? <0.001). Ultrasonography features in ROP are readily detected and described especially in Stage 3 ROP and above. Stage 1 ROP showed negative sign of ultrasound. There is high degree of correlation between the clinical features and ultrasonography features at all stages.